2013
DOI: 10.1038/srep01652
|View full text |Cite
|
Sign up to set email alerts
|

Learning from Nature to Improve the Heat Generation of Iron-Oxide Nanoparticles for Magnetic Hyperthermia Applications

Abstract: The performance of magnetic nanoparticles is intimately entwined with their structure, mean size and magnetic anisotropy. Besides, ensembles offer a unique way of engineering the magnetic response by modifying the strength of the dipolar interactions between particles. Here we report on an experimental and theoretical analysis of magnetic hyperthermia, a rapidly developing technique in medical research and oncology. Experimentally, we demonstrate that single-domain cubic iron oxide particles resembling bacteri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
457
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 498 publications
(489 citation statements)
references
References 66 publications
26
457
0
6
Order By: Relevance
“…Magnetization values were found to be below the 0.5 M S for 40 nm cubic particles (MartinezBoubeta et al 2013). In our study, the M S was lesser for our particle, as smaller particles have smaller magnetization (Martinez-Boubeta et al 2013;Disch et al 2012).…”
Section: Squidmentioning
confidence: 45%
See 1 more Smart Citation
“…Magnetization values were found to be below the 0.5 M S for 40 nm cubic particles (MartinezBoubeta et al 2013). In our study, the M S was lesser for our particle, as smaller particles have smaller magnetization (Martinez-Boubeta et al 2013;Disch et al 2012).…”
Section: Squidmentioning
confidence: 45%
“…Accordingly, there are different transition fluctuations observed. There was a steady increase in the magnetic moment as the temperature increased up to 200 K and a sudden decrease at 300 K, and again an immediate increase up to 300-350 K, and finally a sudden fall at 400 K. The reduction in coercivity was observed mean particle size that was decreased (Martinez-Boubeta et al 2013). Transition fluctuation in magnetic moment probably due to the different molecular arrangements occurred when the particles were formed in the magnetic field.…”
Section: Squidmentioning
confidence: 94%
“…Martínez-Boubeta et al 28 have experimentally demonstrated that highly anisotropic long chains of magnetic nanoparticles give rise to the increased SAR. Very recently, we have achieved higher values of the SAR for the cubic FeO/γ-Fe2O3 nanoparticles as compared to their spherical counterpart (200 vs. 135 W/g at 600 Oe) 29 .…”
Section: Page 16 Of 29 Confidential -Author Submitted Manuscript Nanomentioning
confidence: 99%
“…Kübik Fe 3 O 4 nanoparçacıkların kimyasal yöntem kullanılarak sentezlenmesi Bu sentez işleminde Martinez-Baubeta ve arkadaşlarının 2013 yılında yaptıkları çalışma temel alınmıştır [11]. Örneklerin hazırlanmasında izole edilmiş Schlenk sisteminden, 15 dakika süre ile azot gazı geçirilerek içeride bulunan oksijen gazı dışarıya atıldı.…”
Section: Deneysel çAlışmalarunclassified